1987
DOI: 10.1200/jco.1987.5.12.1912
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between clinical response and in vitro drug sensitivity of primary human tumors in the adhesive tumor cell culture system.

Abstract: The newly described adhesive tumor cell culture system (ATCCS) offers a distinct advantage over other assays in that it has a high plating efficiency requiring low cell inoculum, it affords workable assays in approximately 70% of specimens from the heterogenous tumor types, and it has the ability to assay up to nine drugs at four different concentrations. Clinical correlations based on the ATCCS were obtained in 65 patients undergoing 71 clinical trials. Patients with melanoma, lung cancer, and sarcoma dominat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

1989
1989
2000
2000

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…Each IC 90 value were converted to percentile using these cumulated data. The grade of sensitivity was defined by the percentile values as follows, high sensitive (ഛ15%), moderately sensitive (>15% to ഛ30%), low sensitive (>30% to ഛ50%), and resistant (>50%) as Ajani et al reported [7]. According to our data, gastric cancer cells tended to be highly sensitive to MMC and CDDP, but relatively resistant to ADM and 5-FU.…”
Section: Chemosensitivity To Drugsmentioning
confidence: 80%
See 2 more Smart Citations
“…Each IC 90 value were converted to percentile using these cumulated data. The grade of sensitivity was defined by the percentile values as follows, high sensitive (ഛ15%), moderately sensitive (>15% to ഛ30%), low sensitive (>30% to ഛ50%), and resistant (>50%) as Ajani et al reported [7]. According to our data, gastric cancer cells tended to be highly sensitive to MMC and CDDP, but relatively resistant to ADM and 5-FU.…”
Section: Chemosensitivity To Drugsmentioning
confidence: 80%
“…The ATCCS revealed features of high colony-forming efficiency, which permitted sensitivity testing from small samples, and the assay system consisted of biological analysis of actual cells grown which permitted improved characterization of drug survival curves [5,7,[14][15][16][17]. These features of the ATCCS motivated us to perform the assay for gastric cancer using fresh biopsy specimens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A wide variety of assays to measure the radiosensitivity of tumour cells have been proposed (see Peters et al, 1986, for review) of which the adhesive tumour cell culture system (ATCCS) developed by Baker et al (1986) has been reported as a major advance (Baker et al, , 1988aBrock et al, 1985;Ajani et al, 1987;Malaise et al, 1987;Peters et al, 1987). The growth of cells adhering to a coated or uncoated plastic surface is a standard practice in tissue culture; ATCCS will here refer to the method described by the Houston group.…”
mentioning
confidence: 99%
“…The ATCCS has been developed and investigated by Baker and colleagues for both radiosensitivity and chemosensitivity testing (Baker et al, 1986;Ajani et al, 1987;Fan et al, 1987). An improved method for growth of human tumour cells has been claimed using a coating of cell adhesive matrix (CAM) on the surface of multi-well plates and a comprehensive range of additives in the culture medium.…”
mentioning
confidence: 99%